Estudio comparativo de herramientas de automatización de pruebas de software basado en la implementación de una adecuada estrategia de pruebas - Arequipa Villagómez, Nathaly Elizabeth (2018)
Due to the large number of changes that can occur throughout the development of software, it is necessary to optimize software-testing times. For this reason, you must have some understanding of software automation strategies to be able to select the most appropriate one. Selecting the right strategy depends on the complexity of the program, whether it is in its initial state or it is in a final state. Evaluating your program will help you choose the right software-testing tool. In this academic article, two different software-testing tools were compared with the same program, both in a web and mobile environment. The following software testing tools were: Selenium Web Driver and HP UFT for web pages, Appium and HPE MOBILE CENTER for mobile testing. The comparison was done taking into consideration the advantages and disadvantages that each one has over the other one and providing a graphical representation of all the results between each tool.